125k views
5 votes
An arithmetic sequence has this recursive formula: (a^1 =8, a^n= a^n-1 -6

A.a^n=8+(n-6)(-1)
B.a^n=8+(n-1)(-6)
C.

1 Answer

4 votes

Answer:


a_n = 8 + (n - 1) (-6)

Explanation:

Given


a_1 = 8

Recursive:
a_(n) = a_(n-1) - 6

Required

Determine the formula

Substitute 2 for n to determine
a_2


a_(2) = a_(2-1) - 6


a_(2) = a_(1) - 6

Substitute
a_1 = 8


a_2 = 8 - 6


a_2 = 2

Next is to determine the common difference, d;


d = a_2 - a_1


d = 2 - 8


d = -6

The nth term of an arithmetic sequence is calculated as


a_n = a_1 + (n - 1)d

Substitute
a_1 = 8 and
d = -6


a_n = a_1 + (n - 1)d


a_n = 8 + (n - 1) (-6)

Hence, the nth term of the sequence can be calculated using
a_n = 8 + (n - 1) (-6)

User Richard Hu
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.